Price‐rent ratio in china’s housing market: Proper interval, measurement and an empirical study - Xie, Yuelay; Liu, Hongyu (International Journal of Strategic Property Management, 2010)
It has been a hot topic concerning about whether price bubbles exist in the housing market in several cities in China or otherwise. However, much of the debate lacks convincing evidence. This paper discusses the two factors which may lead the housing price to deviate from its fundamental value: rational bubble and economic irrationality. Also, the paper considers the price‐rent ratio as a valid indicator in reflecting the rationality of the housing price. Based on an international comparative study and the Income Capitalization Method, this paper will show that the proper interval of the price‐rent ratio in China’s housing market should be around 150–200. At the end of this paper, an empirical study will be presented after an alternative measurement method for China’s housing market is proposed. It will illustrate that housing prices in Shanghai and Hangzhou are overvalued while that in Beijing and Guangzhou are comparatively closer to the proper interval. First Published online: 18 Oct 2010